Development rate and growth duration of rice (Oryza sativa) in response to delayed transplanting - KRISHNAN, P; NAYAK, S K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1994-95 at Cuttack on the effect of delayed transplanting on the rate of development and duration of growth in rice (Oryza sativa L.) over 2 sets of seedlings differing in their age at the time of transplanting on alluvial soil (haplaquept). Number of days and of growing degree-days to reach active tillering, panicle initiation, flowering, milky white grain and 80% panicle ripe were computed. Yield, panicle weight and test weight were measured, and straw yield and vegetative growth index were calculated. Correlations were calculated for these values with number of days and with number of growing degree-days at each stage of development. In delayed transplanting, significant correlations occurred between yield factors and growing degree-days, rate of development and duration of growdL Number of days to reach each stage of development was significantly reduced by delayed transplanting, whereas there was no reduction in number of growing degree-days. On entry mean basis, neither number of accumu-. lated growing degree-days nor number of days was correlated with grain yield, straw yield or test weight. Both the parameters could be useful for predicting rate of development and duration of growth; however, since number of growing degree-days is less variable throughout the season, its use is beneficial.